A verdade estética pelo olhar do outro: de Rogério Sganzerla para Orson Welles - De Marco, Cristina (2020)
The american filmaker Orson Welles filmed in Brazil, in 1942, two episodes of a documentary that would be called It's All True, a project developed within the Good Neighbor Policy of the Roosevelt government. The first, Carnival, would tell the origin of the popular brazilian festival. The second, Jangadeiros - Four Men on a Raft, would talk about an epic event that occurred in the previous year (1941) and that was, including an article in Time american magazine. The film, however, was never completed. Orson Welles had to return to his country and never had contact with the filmed material again. About this fact, Santa Catarina's filmmaker Rogério Sganzerla produced four films: Not Everything is True (1986); Language of Orson Welles (1990), Everything is Brazil (1997) and The Sign of the Chaos (2003). I will call them the Tetralogy of Truth. I analyze these films with the help of the concepts of Anthropophagy, coined by Oswald de Andrade in the Man-eating Manifest (1928) and the term developed by the French Gilles Deleuze and Felix Guattari called Body Without Organs. As a result of these analyzes, I arrive at the Aesthetic truth through the eyes of the other: from Rogério Sganzerla to Orson Welles.